What motivates individuals to volunteer in Ebola epidemic response? A structural approach in Guinea - Lonzozou Kpanake; Togba Dounamou; Paul Clay Sorum; Etienne Mullet (BMC, 2019)
Abstract Background The 2014-2016 Ebola epidemic in West Africa placed greater demands on the affected countries' already scarce health workforce. Consequently, governments in the most affected West African countries made appeals for volunteers to join Ebola response programs. Those volunteers played an important yet high-risk role in aiding the victims of the Ebola epidemic and in limiting its spread. However, little is known as to what motivated those volunteers to commit themselves to the Ebola response programs. This information is important for planning for volunteer recruitment strategies during future epidemics. The aim of the present study, therefore, was to identify and assess the motivations that led individuals to volunteer for Ebola response programs in West Africa. Methods The study participants were 600 persons who volunteered through the Guinean Ebola response program during the 2014-2016 epidemic. From February to May 2016, they were presented with a questionnaire that contained 50 assertions referring to possible motives for volunteering in the Ebola response program and indicated their degree of agreement with each of them on a scale of 0-10. The responses were analyzed using factor analysis. Results Seven separable volunteer motivations were identified. "Feeling of patriotic duty" (M = 9.02) and "Feeling of moral responsibility" (M = 8.12) clearly emerged as the most important. Second-tier motivations were "Compliance with authority" (M = 6.66), "Desire to use one's skills for a collective good" (M = 6.49), "Seeking personal growth" (M = 5.93), "Desire to gain community recognition" (M = 5.13), and "Hoping for a career reorientation" (M = 4.52). Conclusions These findings strongly suggest that volunteer recruitment, if needed in future Ebola epidemics, must adopt a multifaceted motivational approach rather than focus on one single motivator. Putting relatively more emphasis on motivational messages referring to patriotic values, as well as to moral responsibility, would likely increase volunteering.